Comparative study of particle size and shape effects on powder packing densities - Mohd Rhafiq Mazlan,; Nashrah Hani Jamadon,; Abu Bakar Sulong,; Mohammad Azlan Aripin,; Fathin Iliana Jamhari,; Farazila Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Uncertainties in powder spreading in powder bed-based additive manufacturing (AM) have posed challenges in the quality and repeatability aspects of manufactured parts. These challenges result in high porosity due to voids existing between the powder bed particles. This work focuses on identifying the uncertainty induced by particle size distribution (PSD) on powder flowability using SS316L as a model material. Various sizes of particles, ranging from 10 μm to 100 μm, as well as spherical and satellite-shaped particles with a bimodal ratio of 70:30, were analyzed. The tapped density, apparent density, and Hausner ratio of each sample will be determined using USP 616. Smaller particle sizes have been shown to reduce both bulk and apparent density. Meanwhile, the shapes of particles also contribute to the packing ability between the powder particles. Satellite powder has been proven to increase the diameter of the powder, consequently enhancing the bulking density of the powder particles. Moreover, bimodal particles have been shown to increase both bulk and tapped density, whereas smaller powder is not able to fill the voids that exist between the larger particles. However, the bulk density decreases as the size ratio between the powder particles increases, indicating that smaller powder is capable of filling the gaps between the particles. When comparing the powder particles in terms of Hausner ratio value, bimodal particles have been shown to cause the poorest flowability with a value of 1.19856. This is due to the fact that the smaller particles between the larger particles increase the friction between the powders. Therefore, this study illustrates how particle size and shape influence powder packing densities, which is crucial for optimizing material design and processing techniques